Mitochondrial Involvement in Migration, Invasion and Metastasis - Denisenko, Tatiana V.; Gorbunova, Anna S.; Zhivotovsky, Boris (Frontiers in Cell and Developmental Biology, 2019)
Mitochondria in addition to being a main cellular power station, are involved in the regulation of many physiological processes, such as generation of reactive oxygen species, metabolite production and the maintenance of the intracellular Ca2+ homeostasis. Almost 100 years ago Otto Warburg presented evidence for the role of mitochondria in the development of cancer. Over the past 20 years mitochondrial involvement in programmed cell death regulation has become clear. Moreover, it has been shown that mitochondria may act as a switchboard between various cell death modalities. Recently, accumulated data have pointed to the role of mitochondria in the metastatic dissemination of cancer cells. Here we summarize the modern knowledge concerning the contribution of mitochondria to the invasion and dissemination of tumor cells and the possible mechanisms behind that and attempt to target metastatic cancers involving mitochondria.